Treatment Success of Drug-Resistant Tuberculosis Patients in Semarang City - Jazilatun, Fina; Ratna Rahayu, Sri; Dwi Cahyani, Tika; Nur Ayu Merzistya, Aufina (Universitas Negeri Semarang, 2024)
Background: The treatment success rate was the number of cured and fully treated tuberculosis cases among all treated and reported tuberculosis cases. In Semarang City, the treatment success rate for drug-resistant tuberculosis in 2016 was 71%, and decreased in 2017 to 43%. The purpose of this study was to determine the factors associated with successful treatment of Drug Resistant Tuberculosis in Semarang City.Methods: Type of research is observational analytic research with case control design. Case samples were tuberculosis patients who were declared cured and complete treatment, control samples were tuberculosis patients who were declared not cured or failed. the number of samples in this study were 23 cases and 23 controls. This research instrument used a questionnaire sheet, bivariate analysis using chi-square analysis techniques.Results: The results showed that factors associated with the successful treatment of drug-resistant tuberculosis were treatment supporter (p<0.05; OR=3.93), the role of drug swallowing superintendent (p<0.01; OR=10.20), medication compliance (p<0.01; OR=8.91), and comorbidity (p<0.05; OR=3.93).Conclusion: Factors that were not associated with successful treatment of drug-resistant tuberculosis were age, gender, education level, Occupations, income, smoking status, nutritional status, drug side effects, staff attitude, and distance health facilities.